УСТЮРТ КЕНГЛИКЛАРИДА ТАРҚАЛГАН “ОЛТИН ТОМИР” ЎСИМЛИГИ ФАРМАЦЕВТИКА СОХАСИ УЧУН “ОЛТИН ЕЧИМ” - Абдуназарова Зулайхо Шарифқуловна; Нуриддинова Нозима Нуриддин қизи (TADQIQOTLAR.UZ, 2023)
Анотатция: Trials of planting 13 types of drought-resistant plants are being carried out in the dry part of the Aral Sea through an innovative approach to strengthening sandslides, reducing the release of toxic aerosol dust from the dry part of the island into the air, and growing seedlings of food plants resistant to desert conditions.